OC-013 Genetic susceptibility to orofacial granulomatosis. (22nd June 2015) - Goel, R; Nayee, S; Escudier, M; Satsangi, J; Mansfield, J; Mathew, C; Prescott, N; Sanderson, J
Abstract : Introduction: Orofacial granulomatosis (OFG) is a rare, disfiguring inflammatory disorder of the mouth where a proportion of cases also have intestinal Crohn's disease (CD). The aetiology remains largely unknown, although there is high prevalence of allergy in OFG with and without CD. Our objective was to investigate whether OFG and CD have shared genetic aetiology or whether OFG is mediated by distinct immune-related genetic susceptibility variants. Method: Patients were clinically assessed and determined to either demonstrate isolated oral manifestations (OFG only) or concurrent intestinal CD (CD/OFG). Genomic DNA from 263 patients was genotyped using the Immunochip, a custom Illumina microarray assessing 196, 524 genetic variants across multiple immune-related disease loci. Patient data was compared to data for 4, 307 population controls from the UKIBD consortium. Statistical analysis was performed using PLINK, a whole genome association analysis program and the R statistical package. Results: Analyses revealed two significant associations (p < 2 × 10 –6 ) within the OFG only cohort with single nucleotide polymorphisms (SNPs) on chromosome 11q13.5 near the LRRC32 gene (p = 1.6 × 10 –9 ) and on chromosome 6 (p = 3.9 × 10 –7 ) within the MHC class I region. The 11q13.5 locus has previously shown association with atopic conditions and the MHC class I region is implicated in numerous allergic and autoimmune diseases, including CD. In addition, a highly suggestive association was detected from the CD/OFG group on chromosome 5p13 (p = 2.5 × 10 –6 ), a known risk locus for CD. Collectively, these results suggest that OFG is influenced by common variants implicated in allergy and immunity, supporting the link between OFG and allergy. However there may also be some overlap with genetic aetiology for CD. Replication in a larger independent cohort is required to substantiate our findings. Conclusion: OFG is likely to be a complex disease mediated by diverse genetic variants, sharing genetic susceptibility with allergic disorders and autoimmune conditions such as CD. Disclosure of interest: None Declared.